Jet production in ep collisions at low Q2 and determination of αs - Aaron, Francisc Dionisie; Sauter, Michel David; Schöning, André; Schultz-Coulon, Hans-Christian (The European physical journal. C, Particles and fields, 2010)
The production of jets is studied in deep-inelastic e+p scattering at low negative four momentum transfer squared 5<Q2<100 GeV2 and at inelasticity 0.2<y<0.7 using data recorded by the H1 detector at HERA in the years 1999 and 2000, corresponding to an integrated luminosity of 43.5 pb−1. Inclusive jet, 2-jet and 3-jet cross sections as well as the ratio of 3-jet to 2-jet cross sections are measured as a function of Q2 and jet transverse momentum. The 2-jet cross section is also measured as a function of the proton momentum fraction ξ. The measurements are well described by perturbative quantum chromodynamics at next-to-leading order corrected for hadronisation effects and are subsequently used to extract the strong coupling αs.
*The H1 Collaboration: F.A. Aaron, M. Sauter, A. Schöning, H.-C. Schultz-Coulon [und 230 weitere Personen]
Im Titel ist die Zahl 2 hochgestellt
Im Titel ist der Buchstabe s tiefgestellt
Gesehen am 15.11.2022